Study on fold formation mechanism and process optimization in multi-directional die forged valve bodies - Longjiang Niu; Yongwan Zhang; Leiyu Zhang; Qingliang Zhang; Weiping Luo; Jingyu Wang; Donghang Liu; Babak Ziaie; Xavier Velay (PLoS ONE, 2025)
Fold defects represent a prevalent and detrimental issue in the multi-directional die forging of complex valve bodies, often resulting in product rejection and increased manufacturing costs. In this study, a three-dimensional thermo-mechanical coupled finite element (FE) model was developed using Forge ® software to simulate the multi-directional die forging process. The “marking grid” and “sensors” functionalities were employed to visualize and track the formation and evolution of fold defects throughout the entire forming process, thereby elucidating the underlying fold formation mechanism. The effects of three key process parameters—initial billet temperature, main punch speed, and friction coefficient between the billet and die—on fold depth and damage value were systematically analyzed. Orthogonal experiments combined with analysis of variance (ANOVA) were conducted to identify the optimal parameter combination. Results indicated that the friction coefficient had the most significant influence on fold formation and damage accumulation, followed by billet temperature, while punch speed had the least impact. The optimal parameters were determined to be a friction coefficient of 0.1, an initial billet temperature of 1200 °C, and a main punch speed of 30 mm/s. Production trials and fluorescent magnetic particle inspection confirmed the absence of fold and crack defects, and the final forged product closely matched the simulation predictions, validating the effectiveness of the optimized process.